THE IMPLEMENTATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN ANTI-CORRUPTION TO SUSTAIN ECONOMIC GROWTH - Muhammad Arfan Pratama (Asia Pacific Fraud Journal, 2020)
Corruption is an extraordinary crime which gives domino effect on government systems. The impacts include low economic growth and high poverty rate. Corruption enriches certain class only so that the budget which is allocated for the development of the country cannot be fully absorbed. Public service facilities for health, education, and administration cannot operate optimally due to the stalled building construction. To increase the economic growth of a country, a structured improvement is needed by involving the role of citizen in monitoring the government system. The development of Information and Communication Technology (ICT) enhances the transparency of ongoing government systems and public services. Studies conducted by Qiang (2009) and Andersen (2009) showed that the implementation of ICT proved to be able to increase economic growth in developing and developed countries with an increase in GDP. Khan and Majeed (2019) also proved that the implementation of ICT and E-Government also increased GDP for Southeast Asian countries in the period 1980-2015. The ICT developments include e-government, big data analysis, blockchain technology, and whistleblowing systems. The implementation of ICT in government systems, such as licensing systems and procurement systems, provides increased transparency and quality so that economic growth also increases. It takes a lot of money to implement ICT in the government system, but it also becomes an opportunity for state officials to abuse their authority. An example of the use of ICT in Indonesia is the procurement of E-ID Cards. Therefore, the integrated whistleblowing system can be sought to guard the benefits of implementing ICT in increasing economic growth.